2018
DOI: 10.1590/s0004-2803.201800000-18
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-10 -1082 a/G (Rs1800896) Polymorphism With Susceptibility to Gastric Cancer: Meta-Analysis of 6,101 Cases and 8,557 Controls

Abstract: BACKGROUND: The promoter -1082 A/G (rs1800896) polymorphism of Interleukin-10 (IL-10) gene have been widely reported and considered to have a significant role on gastric cancer risk, but the results are inconsistent. OBJECTIVE: To clarify the association, we conducted a meta-analysis to investigate the associations IL-10 -1082 A/G polymorphism with gastric cancer. METHODS: Eligible articles were identified by searching databases including PubMed, Web of Science, and Google Scholar up to August 03, 2017. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
(75 reference statements)
2
19
0
3
Order By: Relevance
“…Several cytokines that modulate the immunologic response have been implicated in the development of cancer (12) . Interleukin-10 (IL-10) is a multifunctional cytokine involved in both innate and Association of promoter region polymorphisms of interleukin-10 gene with susceptibility to colorectal cancer: a systematic review and meta-analysis adaptive immune response, and a wealth of evidence supports its regulatory role in carcinogenesis and tumor growth (13,14) . In addition, increased circulating IL10 has been shown in patients diagnosed with different malignancies, such as hepatocellular carcinoma, autoimmune cancers, and leukemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cytokines that modulate the immunologic response have been implicated in the development of cancer (12) . Interleukin-10 (IL-10) is a multifunctional cytokine involved in both innate and Association of promoter region polymorphisms of interleukin-10 gene with susceptibility to colorectal cancer: a systematic review and meta-analysis adaptive immune response, and a wealth of evidence supports its regulatory role in carcinogenesis and tumor growth (13,14) . In addition, increased circulating IL10 has been shown in patients diagnosed with different malignancies, such as hepatocellular carcinoma, autoimmune cancers, and leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased circulating IL10 has been shown in patients diagnosed with different malignancies, such as hepatocellular carcinoma, autoimmune cancers, and leukemia. The IL10 gene (Gene ID: 3586) has been mapped to human chromosome 1q31-q32, spans 5.2 kb and contains five exons (14) . Many SNPs in the promoter and coding region of IL-10 gene were shown to be associated with cancer risk, and also, studies have showed that the genetic variants played important roles in the transcription and protein expression (15) .…”
Section: Introductionmentioning
confidence: 99%
“…The results manifested that the heterogeneity could be mainly attributed by source of controls for CRC and by ethnicity and source of controls for GC. However, CRC and GC have a complex etiology and pathophysiology generated by the interaction of several genes and environmental factors (7,42). Thus, besides the indeterminate number of characteristics that vary among studies, other confounding factors such as age, gender, lifestyle further contribute to between-study heterogeneity (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of CRC and GC is still not fully understood. However, CRC and GC are multifactorial and multistep diseases caused by complex interactions between environmental triggers and genetic factors (6,7). To date, a wide range of gastrointestinal cancer susceptibility gene variations have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, between-study heterogeneity can distort the results of a meta-analysis [39,40]. Several factors, such as diversity in study design, sample size, ethnicity, source of controls, genotyp ing method, and deviation from HWE might contribute to results heterogeneity [41,42]. To identify possible factors that contributed to high heterogeneity, we performed subgroup analysis by ethnicity.…”
Section: Publication Biasmentioning
confidence: 99%